Bioactivity of Cyperus amuricus extracts against hepatocellular carcinoma and molecular docking analysis targeting the PI3K/AKT/mTOR pathway - Thanh Luan Nguyen; Thanh Khoi Tu; Thien-Vy Phan; Chanh M. Nguyen; Khoa D. Nguyen; Minh Quan Pham; Hai Ha Pham Thi (PLoS ONE, 2026)
Cyperus amuricus (Cyperaceae) has exhibited potential anticancer activity against hepatocellular carcinoma (HCC), yet its molecular mechanisms and phytoconstituent interactions with oncogenic pathways remain underexplored. This study integrates in vitro cytotoxicity assays and molecular docking to evaluate the effects of C. amuricus fractionated extracts on HCC, focusing on PI3K/AKT/mTOR signaling axis. The ethyl acetate (EA) fraction selectively inhibited HepG2 cell proliferation (IC 50 = 159.76 µg/mL) with minimal toxicity to normal fibroblasts. Apoptotic features—cell shrinkage, membrane blebbing, nuclear condensation, and DNA fragmentation—were confirmed through DAPI staining and gel electrophoresis. Western blot analysis revealed dose-dependent suppression of phosphorylated Akt and p70S6K, indicating pathway inhibition. Molecular docking identified strong binding affinities between Cyperaceae-derived compounds and PI3K/AKT/mTOR targets, with luteolin 7-O-β-D-glucuronopyranoside-6″-methyl ester blocked PI3K activation, vitexin bound AKT’s allosteric site, and digitoxin targeted mTOR’s ATP-binding pocket, showing comparable binding energies to reference ligands. These findings suggest C. amuricus as a promising candidate for natural product-based HCC therapy.